2008
DOI: 10.1103/physrevb.78.060506
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon superconductivity in LaNiPO

Abstract: We report first principles calculations of the electronic structure, phonon dispersions and electron phonon coupling of LaNiPO. These calculations show that this material can be explained as a conventional electron phonon superconductor in contrast to the FeAs based high temperature superconductors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

104
624
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(732 citation statements)
references
References 24 publications
104
624
3
1
Order By: Relevance
“…It should be noted that, depletion of these states from the near E F clearly indicates an opening up of a pseudogap as the temperature is lowered from 300 K to 77 K. Figure 2(a) shows the calculated total density of states (DOS) over the valence band region. The calculated DOS matches with the earlier theoretical study [21,22] and also with the observed experimental data. Fig 2) corresponds to the experimentally obtained features at 0.1 eV and 0.5 eV, respectively.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It should be noted that, depletion of these states from the near E F clearly indicates an opening up of a pseudogap as the temperature is lowered from 300 K to 77 K. Figure 2(a) shows the calculated total density of states (DOS) over the valence band region. The calculated DOS matches with the earlier theoretical study [21,22] and also with the observed experimental data. Fig 2) corresponds to the experimentally obtained features at 0.1 eV and 0.5 eV, respectively.…”
Section: Resultssupporting
confidence: 88%
“…Peak C at 4 eV is due to the hybridized Fe 3d -Se 4p/Te 5p states while D at 6 eV corresponds to Se 4p/Te 5p states. Our calculations based on the TBLMTO-ASA (fig 2(a)) and also other's calculations [21,22] conform to these assignments. The sharp feature A seen in the case of FeSe transforms into a broadened one for FeTe.…”
Section: Resultssupporting
confidence: 85%
“…Interestingly, a (π, π) nested vector is also consistent with the magnetic striping along [110] direction. 14,46 The addition of excess Fe using a rigid band approximation changes the Table 3 for further details concerning (c) and (d). topology of the Fermi surface, particularly at the Γ point.…”
Section: Magnetic Orderingmentioning
confidence: 99%
“…The two former structures contain well separated chalcogenide valence p and metal 3d states, whereas the latter shows a poorly defined pseudogap with the Te 5p bands moving into the same energy range as the Fe 3d states. 14 Fermi surfaces and phonon dispersion curves were also investigated without accounting for spin polarization. Welz and Rosenberg investigated the electronic structure of stoichiometric tetragonal "FeS" and showed the density of states (DOS) does not follow the Stoner criterion for ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…where more than one determinant is needed for a qualitative description of the system. Such situations arise in bond breaking [1], large π-conjugated molecules where the HOMO-LUMO gap is small [3], transition metal complexes [4] and superconductivity [5]. For such cases, a single Slater determinant gives qualitatively incorrect results.…”
Section: Introductionmentioning
confidence: 99%